Evaluating Functional Capacity in Athletes: A Systematic Review of Measurement Tools and Techniques - Nimrot Manalu; Mei Chintia Haerani; Yusuf Naibaho; Esran Polin Harefa (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This systematic review aimed to evaluate and compare the reliability, validity, and clinical utility of functional capacity assessment tools and techniques used in athletic populations across various sports disciplines. Methods: A comprehensive search of electronic databases (PubMed, CINAHL, SPORTDiscus, Web of Science, and Cochrane Library) was conducted for studies published between January 2000 and September 2024. Studies evaluating functional capacity measurement tools in athlete populations were included. Two independent reviewers assessed methodological quality using the COSMIN checklist, and data extraction was performed using a standardized form. Results: From 1,742 initially identified studies, 87 met the inclusion criteria, evaluating 43 distinct functional capacity assessment tools. Field based tests demonstrated higher ecological validity but lower standardization than laboratory assessments. Sport-specific tools showed greater sensitivity for detecting performance deficits compared to generic assessments. Reliability was highest for technology-assisted measurements (ICC>0.85) compared to observational tools (ICC 0.62-0.79). The Y-Balance Test, Functional Movement Screen, and sport-specific performance batteries emerged as the most comprehensively validated tools across multiple sports. Conclusion: While several valid and reliable tools exist for evaluating functional capacity in athletes, selection should be guided by sport-specific requirements, available resources, and assessment purpose. Multi-dimensional assessment batteries that combine quantitative performance metrics with qualitative movement pattern analysis provide the most comprehensive evaluation of athletic functional capacity. Future research should focus on establishing minimal clinically important differences and developing sport-specific normative data.